2012
DOI: 10.1111/j.1754-4505.2012.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental case manager encounters: the association with retention in dental care and treatment plan completion

Abstract: Little is known about dental case managers as few programs have been scientifically evaluated. The goal of this study was to explore the impact of dental case manager on retention in dental care and completion of treatment plans, while specifically exploring the number of dental case manager encounters. Fourteen programs enrolled people with HIV/AIDS (PLWHA) in dental care and a longitudinal study between 2007 and 2009. The 758 participants had a total of 2715 encounters with a dental case manager over twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Dental case management can encapsulate responsibilities beyond those at just the administrative level, and can include motivational interviewing, health literacy activities, care coordination, community outreach, and education . Studies on dental case management have shown that it leads to improved retention in dental care, completion of treatment plans, and improvements in oral health . In the era of interdisciplinary health‐related practices, medical case management could also potentially play a role in encouraging oral health prevention as well, given its documented ability to help improve overall morbidity and mortality, medication adherence, and continuity of care .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental case management can encapsulate responsibilities beyond those at just the administrative level, and can include motivational interviewing, health literacy activities, care coordination, community outreach, and education . Studies on dental case management have shown that it leads to improved retention in dental care, completion of treatment plans, and improvements in oral health . In the era of interdisciplinary health‐related practices, medical case management could also potentially play a role in encouraging oral health prevention as well, given its documented ability to help improve overall morbidity and mortality, medication adherence, and continuity of care .…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies on dental case management have shown that it leads to improved retention in dental care, completion of treatment plans, and improvements in oral health. 30,33 In the era of interdisciplinary health-related practices, medical case management could also potentially play a role in encouraging oral health prevention as well, given its documented ability to help improve overall morbidity and mortality, medication adherence, and continuity of care. [34][35][36] Such findings underscore the significant role that case management plays in facilitating and maintaining health care utilization and improved disease outcomes amongst underserved population.…”
Section: Discussionmentioning
confidence: 99%